Learning Joomla! 1.5 extension development a practical tutorial on creating Joomla! 1.5 extensions with PHP, written and tested against the final release of Joomla! 1.5 - LeBlanc, Joseph L.; Safari eBooks (Birmingham, U.K. : Packt Pub., 2008)
"The book will show you how to use the Model-View-Controller design pattern, pull in common HTML elements, use JavaScript frameworks, manage users, build configuration panels, internationalize interfaces, and manage database records. General knowledge of PHP is assumed, but previous Joomla! programming experience is not"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Joomla! (Computer file); Web sites -- Authoring programs; Web site development; PHP (Computer program language); Electronic books